INFLUENCE OF VARIOUS RENNET ENZYMES ON TECHNOLOGICAL AND SENSORY PARAMETERS OF BRYNZA - Bilyi, V. Y.; Merzlov, S. V. (Scientific Progress & Innovations, 2022)
The article presents the results of sensory parameters of cheese samples, which were obtained using various rennet enzymes. In the control group of samples for curdling used rennet enzyme of microbial origin. III groups of milk samples (n = 5) were formed for the experiment. In the first experimental group of samples, an enzyme preparation from rennet of dairy calves was used, extracted according to the method of Yu. Ya. Svyridenko. In the second experimental group, an enzyme preparation was used, which was extracted from rennet of dairy calves according to the method of S.V. Merzlov. In both control and experimental groups, each sample was 5.0 dm³. The filtered milk was cooled to 4 ° C and kept for 12 hours. Pasteurization was performed at a temperature of 60-63 ° C for 30 minutes. Pasteurized milk was normalized by mass fraction of fat. Enzyme preparations were added to normalized milk heated to a temperature of 33 ° C by gently stirring it. The clot was cut into cubes of 15-20 mm in size and left alone for 10-15 minutes, then gently mixed for 20-30 minutes to seal and dehydrate. Kneading was performed using stops for 2-3 minutes. Samples were stored at 4 °C with constant ventilation. Samples for sensory analysis were taken at 20, 40 and 60 days of storage. After 60 days of storage, the samples of the control and experimental groups of samples had a sour taste with a pronounced odor of mold, the surface was slippery and had a pronounced yellow color of cheese dough inhomogeneous throughout the mass with a pronounced crust. Samples of the second experimental group had a weak taste and smell of mold, less pronounced tearing of the surface and less pronounced yellow color. The use of rennet enzymes obtained by the method of S. V. Merzlova (II experimental group) helps to increase the yield of the finished product by 7.7% compared to variants where enzymes of microbial origin were used. The use of rennet enzymes obtained by the method of S. V. Merzlova prolongs its storage using brynza technology, which is confirmed by organoleptic indicators.